2016
DOI: 10.1080/11038128.2016.1224271
|View full text |Cite
|
Sign up to set email alerts
|

The linkage between patterns of daily occupations and occupational balance: Applications within occupational science and occupational therapy practice

Abstract: Patterns of daily occupations (PDO) and occupational balance (OB) are recurring phenomena in the literature. Both are related with health and well-being, which makes them central in occupational therapy practice and occupational science. The aim was to review how PDO and OB are described in the literature, to propose a view of how the two constructs may be linked, and elaborate on how such a view may benefit occupational science and occupational therapy. The literature was analysed by latent and manifest conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 94 publications
5
78
1
3
Order By: Relevance
“…Based on focus groups interviews with 19 women with stress-related disorder, Håkansson and co-workers also suggested a relationship between occupational balance and well-being mediated by manageability, control, and a harmonious occupational repertoire (3). This linkage makes the concept of occupational balance essential in occupational therapy practice as well as in occupational science (4).…”
Section: Introductionmentioning
confidence: 99%
“…Based on focus groups interviews with 19 women with stress-related disorder, Håkansson and co-workers also suggested a relationship between occupational balance and well-being mediated by manageability, control, and a harmonious occupational repertoire (3). This linkage makes the concept of occupational balance essential in occupational therapy practice as well as in occupational science (4).…”
Section: Introductionmentioning
confidence: 99%
“…In general, perceived organisational support, such as having a clear structure for handover and co-worker and supervisor support could be positive resources to prevent stress-related disorders (26). To experience that one does not have enough resources can, however, lead to work-family conflict (17) and occupational imbalance (9).…”
Section: The Results In Relation To Other Studiesmentioning
confidence: 99%
“…A recent study also showed an association between lack of engagement in valued occupations, little variation between the occupations and high C-Reactive Protein (CRP) among people with Rheumatoid Arthritis (8). Furthermore, an individual´s experience of occupational balance is influenced by the demands and resources in the environment in which he or she lives and acts (9), for example the work environment. It is therefore of interest to study if organisational factors are associated with occupational balance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of the linkage of the two concepts 'patterns of daily occupations' and 'occupational balance' the authors described the concepts as separate but interacting phenomena (Eklund et al, 2017). An individual's pattern of daily occupations is influenced by time, space, and an arrangement of temporal and spatial elements connected with experiences.…”
Section: Activity Patternmentioning
confidence: 99%